Effect of lecturer’s transformational leadership on students’ employability: Malaysian technical and vocational education & training institutions - Omar, Intan Marfarrina; Zulazmi, Nur Iylia Liyana; Ladin, Che Aleha (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2019)
As the economy of Malaysian government has transformed from a typical economy to human capital economy, the demand for Technical and Vocational Education & Training (TVET) institutions as a platform to develop human capital is also increasing. TVET based institutions in Malaysia are known as formal and informal learning sector which provide youthful people with the expertise and skills needed in the work sector. However, TVET-based qualifications and careers in Malaysia are perceived poorly and does not receive recognition in the workplace in terms of employability. These institutions cannot achieve their predetermined goals without effective leadership as the success and failure of the objectives depend on lecturers. Over the last three decades, transformational leadership has achieved legitimacy that has been showed to be an effective and influential enabler especially in developing employees’ attitudes and behaviours. Thus, the aim of present research is determining the role of lecturer’s transformational leadership in effecting students’ employability. This study was conducted in ten (10) Technical and Vocational Education & Training (TVET) institutions located at Peninsular Malaysia, Sabah and Sarawak. A total of 350 final year students were involved in this research which used the quantitative research design approach. Pearson correlations, linear regression and multiple regressions analysis were used to analyse the collected data. The findings indicated that lecturer’s transformational leadership significantly and positively correlated with students’ employability. In addition, the result also indicated that students’ employability can be affected by role of lecturer’s transformational leadership style. Based on the findings, it is indicated that lecturers must display an effective inspirational motivation, idealized influence, individualized consideration and intellectual stimulation which will then stimulate employability development among students especially in TVET institutions. © 2019, University of Malaya. All rights reserved.